A case of thyroid hemiagenesis with thyroiditis - Shrestha, Sandeep; Maharjan, Shova (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Thyroid hemiagenesis is a very rare congenital abnormality, in which one thyroid lobe fails to grow. Most of the patients are usually associated thyroid disease. The prevalence of thyroid hemiagenesis ranges between 0.05% and 0.2% within the literature. We hereby report a case of 29 years male with left lobe thyroid hemiagenesis with right lobe thyroiditis presented with a feature of hyperthyroidism. Thyroid hemiagenesis can be associated with hyper or hypothyroidism. In our case patient had a feature of hyperthyroidism with dearranged TFT. In our case we detected thyroid hemiagensis incidentally with the help of ultrasonography. Ultrasonography was the investigation that detected thyroid hemiagenesis. Ultrasonography is the most cost-effective means of diagnosing thyroid hemiagenesis. We further performed the thyroid scan to detect any hyperfunctioning thyroid gland or ectopic thyroid. Thyroid scan helped detect thyroiditis in the right thyroid lobe.